Treatment of Arachnoid Cyst With Spontaneous Hemorrhage With Atorvastatin - Liu, Bei; Wang, Chao; Qu, Yan (Frontiers in Pharmacology, 2019)
As one of the common neurological diseases, pediatric middle fossa arachnoid cysts（MFACs) can develop intracystic hemorrhage and subdural hematoma. Risk factors for pediatric arachnoid cyst rupture/hemorrhage is very complicated in mechanism. Although surgery is the first choice for children with MFACs and subdural hematoma, the rate of recurrence of the subdural hematoma is very high after 1 or more surgeries. Atorvastatin has proven to be a bold and safe choice in the management of subdural hematoma with mild symptoms. The present study has described a 7-year-old child with a recurrent rupture of arachnoid cyst develops into a subdural hematoma. We demonstrate that atorvastatin is safe and effective in pediatric patient who has failed surgical treatment of middle fossa arachnoid cyst and subdural hematoma. The patient received atorvastatin monotherapy, once daily for the first week, with an initial dose of 5 mg, followed by 10 mg once daily for 7 weeks. In the third month after the initial treatment, the neurological function recovered, and the hematoma completely resolved. This case report supports the concept that atorvastatin can promote the absorption of subdural hematoma.